Are radiographic indices reliable indicators for quantitative bone mineral density and vitamin D status after femoral neck fractures? A retrospective study in 112 elderly patients. Issue 1 (December 2015) - Yeo, Andy; Ahrberg, Annette; Theopold, Jan; Ewens, Sebastian; Borte, Gudrun; Josten, Christoph; Fakler, Johannes
Abstract Background Radiographic parameters and indices obtained from hip x-rays are a potential tool to promptly estimate bone quality in elderly hip fracture patients. Preoperative decision in whether to use cemented or cement augmented implants might be supported by this information and thus improve patient safety. Subsequently, this study was conducted to evaluate radiographic parameters as a prescreening tool for bone quality. Methods A retrospective analysis of 112 elderly patients with a femoral neck fracture after low-energy trauma was performed (81 % female, 19 % male). Three radiological indices were calculated on hip x-rays: cortical index antero-posterior CTI (ap), cortical index lateral CTI (lat) and canal to calcar ratio CCR. These indices were analyzed for correlations with DXA T-Scores and serum 25-hydroxyvitamin D (25(OH)D) using the Spearman test. Results Median age of patients was 80 (IQR 72–86) years. A linear correlation was found for CTI (lat) and T-Score at the total hip (p  < 0.001, r  = 0.589), femoral neck (p  = 0.005, r  = 0.405) and the lumbar spine (p  = 0.002, r  = 0.299). A significant correlation was also indicated between CTI (lat) and 25(OH)D (p  = 0.002, r  = 0.293). CTI (lat) at a cut-off level of 0.4 showed a sensitivity of 79 % and a specificity of 56 % in predicting a T-score ≤ −2.5 at the total hip. Gender specific analysis revealed a higher sensitivity (100 %) and specificity (73 %) of CTI (lat) at a cut-off level of 0.4 for men. For severe vitamin D deficiency (<10 ng/ml) sensitivity and specificity were 75 % and 65 %. Conclusion Radiographic indices as the CTI (lat) exhibit a direct correlation to BMD and serum 25OH vitamin D levels. A CTI (lat) cut-off level of 0.4 is recommended for identifying patients at risk of osteoporosis expressed by T-Scores ≤ −2.5 and severe vitamin D deficiency.